Beliefs, Barriers, and Preferences of European Overweight Women to Adopt a Healthier Lifestyle in Pregnancy to Minimize Risk of Developing Gestational Diabetes Mellitus: An Explorative Study. (14th January 2016) - Jelsma, Judith G. M.; van Leeuwen, Karen M.; Oostdam, Nicolette; Bunn, Christopher; Simmons, David; Desoye, Gernot; Corcoy, Rosa; Adelantado, Juan M.; Kautzky-Willer, Alexandra; Harreiter, Jürgen; van Assche, Frans Andre; Devlieger, Roland; et al.
Abstract : Introduction . We explored beliefs, perceived barriers, and preferences regarding lifestyle changes among overweight European pregnant women to help inform the development of future lifestyle interventions in the prevention of gestational diabetes mellitus. Methods . An explorative mixed methods, two-staged study was conducted to gather information from pregnant European women (BMI≥ 25 kg/m 2 ). In three European countries 21 interviews were conducted, followed by 71 questionnaires in six other European countries. Content analysis and descriptive and chi-square statistics were applied (p < 0.05 ). Results . Women preferred to obtain detailed information about their personal risk. The health of their baby was a major motivating factor. Perceived barriers for physical activity included pregnancy-specific issues such as tiredness and experiencing physical complaints. Insufficient time was a barrier more frequently reported by women with children. Abstaining from snacking was identified as a challenge for the majority of women, especially for those without children. Women preferred to obtain support from their partner, as well as health professionals and valued flexible lifestyle programs. Conclusions . Healthcare professionals need to inform overweight pregnant women about their personal risk, discuss lifestyle modification, and assist in weight management. Lifestyle programs should be tailored to the individual, taking into account barriers experienced by overweight first-time mothers and multipara women.